High-Precision Digital Image Correlation for Investigation of Fluid-Structure Interactions in a Shock Tube - Lynch, K. P.; Jones, E. M. C.; Wagner, J. L. (Experimental mechanics, 2020)
Background: Structural response measurements are challenging in aerodynamic testing environments due to high-speed requirements, facility vibrations, and the desire for non-intrusive measurements. Objective: This study uses stereo digital image correlation (DIC) to investigate the response of a jointed beam under aerodynamic loading in a shock tube. Methods: The incident shock subjects the beam to an impulsive frontal load followed by periodic transverse loading from vortex shedding. Several considerations necessary to realize high-precision are addressed: first, a hybrid stereo camera calibration accounted for tangential distortions when imaging through thick windows. Second, a measurement bias from Xenon flash-lamp light sources was identified and removed using laser illumination. Third, facility motion was mitigated by vibration isolation and appropriate signal filtering. Finally, aero-optical distortions from turbulence were removed using a low-order reconstruction. Results: The resulting displacement data has a noise floor of approximately ± 1 μm at 20 kHz sampling rate. The reduction of primary noise sources allows a transient structural response on the order of 10–40 μm to be quantified. The highest vibrations occurred when the vortex shedding frequency matched the beam’s natural frequency. Conclusion: the noise reduction techniques described allow for structural measurements requiring high-precision, non-intrusive displacement data to be performed in aerodynamic environments.